OPTIMIZATION GEOLOGICAL STUDIES STAGES FINANCING IN DOMESTIC PRACTICE - Balega, A.; Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The system of organization and financing of geological exploration works was investigated in separate stages. A comparison of the stages and their financial support in Ukraine and abroad has been carried out. In general, the stages correspond to the schemes recommended by the United Nations (UN) as international, but have their own specificity in terms of prospecting and general exploration. The objects, subjects and main sources of financing of works in accordance with the stages of the geological exploration works were defined. The level of state and non-state expenditures in the development of mineral base of Ukraine is fixed by the National program of development of mineral base of Ukraine by 2030; it is 13.8 % and 86.2 % respectively. The structure of public expenditures within the stages of the geological exploration works was investigated. The National program of development of mineral base of Ukraine by 2030 does not directly reflect the financing of the of geological exploration works by stages. According to the results of the sample, which is reflected and systematized, it is determined that the state budget provides the work of all three stages from the geological study of the territory to the exploration works. Geological exploration works funded by state funds in Ukraine are executed exclusively by state enterprises. Comparison of the financing indicators of the Program up to 2030 with the distribution of the main geological risks and general risks of mining business was conducted. At the first stage of the geological exploration works, high geological risks are accompanied by moderate mining risks and insignificant specific costs for obtaining geological information; public funding for these activities is concentrated at 9.91 % of the total funding. Stage II of the geological exploration works is accompanied by a higher than average indicator of geological risk, high risk of mining business and significant costs, with 65.71 % of government funding concentrated on these activities. The lowest geological risks and risks of mining business are inherent in Stage III of the geological exploration works, which is the most capital intensive, and whose financing is concentrated 16.7 % of state funding. The geopolitical challenges have led to the need for clarification of the work in the National program of development of mineral base of Ukraine by 2030. There were: actualization of the objects of the geological exploration works, the exclusion from the state financing of the detail exploration (stage III of the geological exploration works) and the concentration of such funding in prospecting and general exploration (stage II of the geological exploration works) in order to identify investment-attractive objects for their further auctioning.